A Clean and Efficient Method for the Synthesis of 3-Aroyl-2,4,6-triaryl-4-hydroxy-1,1-cyclohexanedicarbonitriles in Water - Wang, Ai-Qing; Jin, Tong-Shou; Liu, Li-Bin; Cheng, Zhao-Li; Li, Tong-Shuang (Asian Journal of Chemistry, 2010)
A clean and efficient chemistry route to the synthesis of 3-aroyl-2,4,6-triaryl-4-hydroxy-1,1- cyclohexanedicarbonitriles using hexadecyltrimethyl ammonium bromide (HTMAB) as the catalyst (5 mol %) in aqueous media is described. This method provides several advantages such as neutral conditions, high yields and simple work-up procedure. In addition, water was chosen as a green solvent.